MENINGKATKAN PEMBELAJARAN LOMPAT JAUH GAYA JONGKOK MELALUI PERMAINAN PAKARANJANG SISWA SMPN 2 SUNGAI KAKAP - Ridwan Ridwan; Victor G Simanjuntak; Mimi Haetami (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2018)
Abstract:The problem in this research is how the model of long jump style jump from pakaranjang game on grade VII students SMPN 2 Sungai Kakap Kabupaten kuburaya. The purpose of this study is to improve learning achievement or learning in the long jump style of squat from game pakaranjang. This study uses classroom action research which is the basis for improving the learning that will be produced, with the following steps: 1) Planning; 2) implementation; 3) observation; 4) reflection; Subjects in use as many as 28 students. Data were collected by questionnaire / questionnaire and test each cycle From the results of the study In the preliminary test before the action was seen that the value of learning style long jump squat class 64 and the number of percentage of classical completeness only reached 25%. In the first cycle action with the game approach pakaranjang can improve learning long jump style squatting obtained average learning outcome 74 with 64% classical mastery. In the second cycle action with the game game pakaranjang can improve learning long jump style squat obtained average learning outcomes 77 with classical completeness increased by 96% and the value of student activity observation the better. Keywords: Long Jump, Squatting Style, Pakaranjang Game.